(untitled) (American Journal of Technology and Applied Sciences, 2024)
In this research work, the state of atmospheric air was studied, it was noted that air pollution by industrial enterprises is one of the significant problems in the field of environmental protection today. It has been studied and noted that reducing the emission of pollutants into the atmosphere from sources of industrial enterprises is possible using the latest technical solutions in the field of non-waste technologies; this in turn is associated with high costs and complete re-equipment of certain industries. An alternative solution to the problem of atmospheric air pollution by industrial emissions of harmful gases is the effective and scientifically based use of dust and gas purification devices (DGCD). It is noted that the qualitative characteristics of emissions of pollutants into the atmospheric air are divided into two groups. The main types of pollutants formed by greenhouse gases are given. Classifications of sources of emissions from industrial enterprises are given. It has been revealed that waste gases from stationary sources of industrial enterprises make a huge contribution to environmental pollution, in particular air pollution, contribute to the formation of unfavorable living conditions for living organisms in the zone of formation and dispersion, have a negative effect on the human body, and play a huge role in the formation of the greenhouse effect, which leads to global warming. In this regard, reducing, and in some cases preventing the formation and dispersion of pollutants in the atmospheric air is an urgent and in demand task today.